The Problem of Animal Rights in Selected Works by Dorota Probucka - Joanna Glensk (Studia Ecologiae et Bioethicae)
This article presents the idea of animal rights as perceived by a Polish philosopher and ethicist, Dorota Probucka. It is divided into three sections that delve into the development and significance of animal rights from the perspectives of both proponents and critics of the idea. The first section provides an overview of the turning points in the history and evolution of animal rights, referring to the main thinkers who had the fundamental impact on their development. The second part defines the concept of animal rights and explains why extending fundamental rights to at least some non-human beings is important from both moral and legal perspectives. The third part compares the arguments of the proponents and opponents of the idea of granting basic rights to animals. The philosophers’ positions presented by Probucka prove that beings capable of suffering, regardless of their intellectual abilities, deserve moral consideration. This stance is supported by numerous arguments from various fields of science, demonstrating the degree of awareness and emotional complexity of animals. These arguments should contribute to the recognition of animal rights within a moral and legal context. The article also emphasizes the need for legal reforms, including the need to introduce formal legal structures, such as the appointment of the so-called Animal Rights Ombudsman, who could represent animals at an institutional level. Considering the growing bioethical and biocentric awareness, the article emphasizes the need to redefine our attitude towards animals. It also postulates the necessity of implementing legal reforms that will make animals full participants of the moral community, which is of key importance for the future of both people and animals on our planet.